Viral load profiles in drug users with asymptomatic HIV infection and normal CD4 cell counts (Medical Journal of Indonesia, 2002)
Since the year 2000 there has been a steep increased in the number of HIV/AIDS patients in Indonesia, coming mostly from intravenous drug users. Antiretroviral treatment has been proved to decrease mortality and increase quality of life of HIV/AIDS patients. The treatment is given according to clinical condition of the patients, number of CD4 and viral load. In this study, CD4 and viral load were examined in 71 asymptomatic HIV patients originated from injecting-drug users. CD4 counting was performed by indirect immunoflouresence method using monoclonal antibody, and viral load was tested using PCR technique. Among 56 patients who has the number of CD4 more than 200/mm3, 30 patients (55.4 %) has viral load more than 55,000 copies/ml and 35.7% has viral load 5,000-55,000 copies/ml. Correlation between the number of CD4 and viral load gave the r value of 0.194. It is concluded that there is no association between the number of CD4 and viral load in drug user HIV/AIDS patients. The treatment of HIV/AIDS for these patients should be given according to the viral load. (Med J Indones 2002; 11: 143-7)Keywords: viral load, CD4, injecting-drug user